2021
DOI: 10.12674/ptk.2021.28.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction and Evaluation for Classification Models of Injurious Falls Based on Surface Electromyography

Abstract: Classification Datamining Electromyography Falls Injurious falls Muscle activationBackground: Only 2% of falls in older adults result in serious injuries (i.e., hip fracture).Therefore, it is important to differentiate injurious versus non-injurious falls, which is critical to develop effective interventions for injury prevention. Objects:The purpose of this study was to a. extract the best features of surface electromyography (sEMG) for classification of injurious falls, and b. find a best model provided by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, Lim and Choi [49] suggested that SVM showed higher accuracy than DT for 2 impurity criteria. Therefore, future studies, including various machine learning algorithms (i.e., Naïve Bayes, K-nearest neighbor, Random Forest, Convolutional Neural Network), might help find optimal algorithms for fall-risk classification models using IMU sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lim and Choi [49] suggested that SVM showed higher accuracy than DT for 2 impurity criteria. Therefore, future studies, including various machine learning algorithms (i.e., Naïve Bayes, K-nearest neighbor, Random Forest, Convolutional Neural Network), might help find optimal algorithms for fall-risk classification models using IMU sensors.…”
Section: Discussionmentioning
confidence: 99%